2009
DOI: 10.1016/j.virol.2008.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Mousepox in the C57BL/6 strain provides an improved model for evaluating anti-poxvirus therapies

Abstract: The intranasal lethal mousepox model employing the A/Ncr mouse strain is used to evaluate anti-orthopoxvirus therapies. These infections mimic large droplet transmission and result in 100% mortality within 7-10 days with as little as 1 PFU of ectromelia virus. Unlike the A/Ncr model, humans are less susceptible to lethal respiratory infections with variola virus and monkeypox virus as demonstrated by their lower mortality rates. In this study we show that a low dose intranasal infection of C57BL/6 mice results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 39 publications
3
58
0
Order By: Relevance
“…2 and 3). Parker et al (2009) have shown that following f.p. infection of C57BL/6 mice with 100 PFU f.p.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). Parker et al (2009) have shown that following f.p. infection of C57BL/6 mice with 100 PFU f.p.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of genes encoding WV-specific proteins in VACV, such as A36, B5, and A34, also lead to highly attenuated infections in mice (21,38,51,71). The intranasal route of inoculation used in most of these studies mimics large-droplet transmission of smallpox in humans, leading to a systemic disease that shares similarities with smallpox disease progression (3,46,50). However, intranasal infection of mice with VACV WR requires large doses (10 4 to 10 6 PFU) to achieve substantial mortality (21,38,51), which may not be reflective of the doses of variola virus required to cause disease and death in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, advantages to using a murine MPXV model for therapeutic development include: (i) biomarkers of disease progression have been established in the mousepox model and can be readily applied to the MPXV stat1 Ϫ/Ϫ mouse model (38); (ii) reagents are readily available, and the biology and genetics of the mouse are well understood; (iii) early in the drug development plan, mice are invariably used to acquire efficacy, toxicity, and pharmacokinetic/pharmacodynamic data; and (iv) MPXV itself causes a natural disease in humans, unlike VACV and ECTV, which are used in other mouse models.…”
Section: Discussionmentioning
confidence: 99%